2009
DOI: 10.2478/v10078-009-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Exercise Motives of Adolescents and Young Adults

Abstract: Recreational Exercise Motives of Adolescents and Young AdultsThis study examined the motives for taking part in recreational exercise/sporting activities based on a sample of Turkish young people. Secondly, gender and age group differences with motivational dimensions were investigated. A total of 298 members of 6 Youth Centers voluntarily participated in this study. The Recreational Exercise Motivation Measure (REMM) was administered to all participants. Two × two MANOVA revealed significant main effect for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 18 publications
2
33
0
6
Order By: Relevance
“…Parallel with this study, Ebben and Brudzynski (2008) found that maintaining fitness and health were the two most reported motives for the college students. Besides, in the study of Caglar, Canlan and Demir (2009) health motive was also found as the most important participation motive, whereas competition motive was reported as the least important participation motive for Turkish adults.…”
Section: Discussionmentioning
confidence: 79%
“…Parallel with this study, Ebben and Brudzynski (2008) found that maintaining fitness and health were the two most reported motives for the college students. Besides, in the study of Caglar, Canlan and Demir (2009) health motive was also found as the most important participation motive, whereas competition motive was reported as the least important participation motive for Turkish adults.…”
Section: Discussionmentioning
confidence: 79%
“…This means that they started very young and continue playing and competing, although they will never make a living out of football. Their motives should be similar to the ones found in amateur footballers: health and enjoyment [13] and active adults: mastery and physical fitness [14]. Therefore, practice should never be too strenuous.…”
Section: Discussionmentioning
confidence: 94%
“…Amateur football players enjoy practice, because they feel connected to the sport, but it cannot be too demanding or they will quit. For these individuals football is a hobby, not a profession, and their motivation to be involved is primary linked to health, mastery and enjoyment [13,14]. If practice becomes too strenuous, it also becomes less fun.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, they do represent a culture that is quite different from the Australian culture in which the motivation questionnaires (REMM, PALMS) were developed. The REMM and PALMS have now been examined in Australia [45,47], Turkey [44], Finland [18], Israel [48], and now Malaysia with a high degree of consistency and stability, suggesting that the underlying factors measured by these instruments are motives that apply across cultures and languages. This provides support for the factorial invariance of the PALMS.…”
Section: Discussionmentioning
confidence: 99%